1993
DOI: 10.1111/j.1365-2273.1993.tb00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Day-case adenoidectomy?is it safe?

Abstract: A controlled prospective study was performed on 429 consecutive children undergoing adenoidectomy, of which 263 were day-cases. Adenoidectomy was done alone, or in combination with other minor procedures. There was only one reactionary haemorrhage in each group, and these were early and easily recognized by the recovery staff. No other significant complication was seen. Adenoidectomy in children as a day-case procedure is safe and cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Propofol infusion, Ondansetron). A locally published audit report (Oxford Regional Audit Office, April 1993) of day surgery throughout the Oxford Region in 1993 by one of the authors (PMB) found only a few sporadic adenoidectomies being performed, but in the last few years several papers have appeared suggesting the procedure is safe (Yardley, 1962;Ahmed et al, 1993;Leighton et al, 1993;Tewary, 1993). The operation has gained quite wide acceptance amongst otolaryngologists, particularly as a protocol-led procedure, and 243 were recorded here with an admission rate that almost meets the College guidelines.…”
Section: Outcomementioning
confidence: 99%
“…Propofol infusion, Ondansetron). A locally published audit report (Oxford Regional Audit Office, April 1993) of day surgery throughout the Oxford Region in 1993 by one of the authors (PMB) found only a few sporadic adenoidectomies being performed, but in the last few years several papers have appeared suggesting the procedure is safe (Yardley, 1962;Ahmed et al, 1993;Leighton et al, 1993;Tewary, 1993). The operation has gained quite wide acceptance amongst otolaryngologists, particularly as a protocol-led procedure, and 243 were recorded here with an admission rate that almost meets the College guidelines.…”
Section: Outcomementioning
confidence: 99%
“…Adenoidal haemorrhage is the most common complication of adenoidectomy, occurring in ≈0.006–1.5% 1–7 of patients following curettage. Traditionally, haemostasis is achieved by diathermy using a mirror, packing with an adrenaline soaked gauze, or tamponade with a post‐nasal pack.…”
mentioning
confidence: 99%
“…In the UK in 1990, less than 1.5% of adenoidectomies alone were carried out as day-case procedures [5]. However, published data has confirmed that daycase adenoidectomy is not only a safe procedure, but has a high level of parental acceptability and low degree of parental anxiety and concern [6,7,12,13]. The current constraints to day-case adenoidectomy are limited to patient fitness or unfavourable social circumstances and rural geographical limitations.…”
Section: Discussionmentioning
confidence: 94%
“…In 1993, the Chief Medical Officer of England and Wales set a target aiming for 50% of all surgery to be daycases by 2000 [3]. Several studies support day-case adenoidectomy as a safe and cost-effective procedure [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%